Management of wage fund of civil servants: international standards and foreign experience - Сєвідова, І. О.; Sievidova, I. O.; Iryna Sievidova (Innovative educational technologies: European experience and its application in training in economics and management : Proceedings of scientific and pedagogical internship (Riga, Latvia, 13 February – 26 March, 2023, ). - Riga, Latvia : Baltija Publishing, 2023. - P. 324-326, 2023)
У результаті проведеного дослідження систематизовано нормативно-правові засади, що визначають сутність управління фондом оплати праці, визначено методи та етапи управління фондом оплати праці як однієї зі складових державного регулювання організація оплати праці. Визначено, що спеціальні міжнародні законодавчі акти спрямовані на встановлення рівних прав працівників органів державного управління з метою уникнення дискримінації за професійними ознаками та родом занять. Також визначене в міжнародних нормативно-правових актах регулювання та фінансове забезпечення фонду оплати праці в органах державного управління підтверджує прагнення різних соціальних груп до рівноправного використання наявних можливостей для підвищення рівня життя.

As a result of the conducted research, the regulatory and legal principles that determine the essence of the management of the wage fund were systematized, the methods and stages of the management of the wage fund were determined as one of the components of the state regulation of the wage organization. It was determined that special international legislative acts are intended to establish equal rights for public administration employees, with the aim of avoiding discrimination based on professional factors and type of occupation. Also, the regulation and financial support of the labor remuneration fund in state administration bodies defined in international regulatory legal acts confirm the desire of different social groups for equality in the use of existing opportunities to improve their standard of living.

В результате проведенного исследования систематизированы нормативно-правовые принципы, определяющие сущность управления фондом оплаты труда, определены методы и этапы управления фондом оплаты труда как одной из составляющих государственного регулирования заработной платы. организация заработной платы. Определено, что специальные международные законодательные акты призваны установить равные права для служащих государственного управления с целью недопущения дискриминации по профессиональным признакам и роду занятий. Также регулирование и финансовое обеспечение фонда оплаты труда в органах государственного управления, определенные в международных нормативных правовых актах, подтверждают стремление различных социальных групп к равноправию в использовании существующих возможностей повышения своего уровня жизни.
Keywords: фонд оплати праці; управління фондом оплати праці; міжнародні нормативно-правові акти; management of the wage fund; international legal acts; управление фондом оплаты труда; международные нормативно-правовые акты